Fluorescent Multiplex Immunohistochemistry Coupled With Other State-Of-The-Art Techniques to Systematically Characterize the Tumor Immune Microenvironment - Boisson, Anaïs; Noël, Grégory; Saiselet, Manuel; Rodrigues-Vitória, Joël; Thomas, Noémie; Fontsa, Mireille Langouo; Sofronii, Doïna; Naveaux, Céline; Duvillier, Hugues; Craciun, Ligia; Larsimont, Denis; Awada, Ahmad; et al. (Frontiers in Molecular Biosciences, 2021)
In recent years, expanded knowledge of the interactions between tumor cells and their microenvironment has revolutionized cancer treatment, including the development of immunotherapy. Immune cells are an important component of the tumor microenvironment that can influence progression and immunotherapy responses; although the majority of patients experience minimal or no clinical benefit from the latter. Technological advances that help to decipher the complexity and diversity of the tumor immune microenvironment (TIME) are increasingly used in translational research and biomarker studies. Techniques that facilitate TIME evaluation include flow cytometry, multiplex bead-based immunoassays, chromogenic immunohistochemistry (IHC), fluorescent multiplex IHC, immunofluorescence and spatial transcriptomics. This article provides an overview of representative outputs and discusses applications, advantages and challenges for each approach in evaluating the TIME and any potential for clinical applications. Immune-profiling of a HER2+ breast cancer analyzed by flow cytometry, chromogenic and fluorescent multiplex IHC was used to illustrate these points. A luminal B breast tumor was analyzed by spatial transcriptomics to reveal additional insight from this technology. Finally, we detail how a multiplex panel identifying proliferating B cells, TFH and TFR cells, all associated with tertiary lymphoid structures, was developed.